Ectopic cervical thymoma: a rare entity in an unusual location - Balmoori, Nived R.; Sreekanth, K.; R., Arun S. Rajan A.; Sai, Chilukuri R.; K., Manjula V. (International Surgery Journal, 2025)
Ectopic cervical thymoma is an extremely rare occurrence, with few reported cases in literature. Thymomas typically arise in the anterior mediastinum, and their presence in the cervical region poses significant diagnostic challenges. Given its rarity, it is often misdiagnosed as other neck masses, such as metastatic lymphadenopathy, neurogenic tumors, or thyroid lesions. This report presented a case of a 57-year-old male who presented with a right upper neck mass, which was progressively increasing in size over several months. The patient underwent thorough clinical and radiological evaluation but the results were inconclusive. Ultrasound guided core needle biopsy was suggestive of spindle cell tumour. Neck exploration and surgical excision was performed. Intraoperatively, a well-encapsulated lesion was identified in the right level II neck region, closely adherent to surrounding structures. Complete excision was achieved without complications. Histopathological examination, supplemented by immunohistochemistry (IHC), confirmed the diagnosis of an ectopic cervical thymoma. Ectopic cervical thymomas are rare and often pose a diagnostic dilemma due to their unusual location and overlap with other neck masses. Preoperative identification is difficult, making histopathology and IHC essential for definitive diagnosis. Complete surgical excision remains the mainstay of treatment, offering good prognosis. Increased awareness of this rare entity can aid in early recognition and appropriate management.